2009
DOI: 10.1080/13547500903075218
|View full text |Cite
|
Sign up to set email alerts
|

Soluble interleukin-2 receptor serum level is a useful marker of hidradenitis suppurativa clinical staging

Abstract: Hidradenitis suppurativa (HS) is a recurrent, debilitating suppurative skin disease. The major challenge is the choice of optimal treatment. Assessment of treatment effectiveness is currently associated with clinical observations of disease activity based on Hurley's or Sartorius' grading system. Detailed examination of patients with HS and evaluation of disease severity is frequently time-consuming and undoubtedly subjective. With regard to these factors, there is a need for laboratory findings that will help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 39 publications
4
27
0
Order By: Relevance
“…However, in the light of our study, it may be presumed that the increase in systemic inflammatory processes in HS sufferers, expressed as a significant increase in C-reactive protein and circulating proinflammatory cytokines (e.g. TNF-α), may possibly lead to impairment of endothelial repairing processes, resulting in poorer endothelial integrity and defective endothelial function [25,26]. Such dependences were already observed in other studies.…”
Section: Discussionsupporting
confidence: 57%
“…However, in the light of our study, it may be presumed that the increase in systemic inflammatory processes in HS sufferers, expressed as a significant increase in C-reactive protein and circulating proinflammatory cytokines (e.g. TNF-α), may possibly lead to impairment of endothelial repairing processes, resulting in poorer endothelial integrity and defective endothelial function [25,26]. Such dependences were already observed in other studies.…”
Section: Discussionsupporting
confidence: 57%
“…Matusiak et al 8,10 reported in 2 studies There was a significant correlation between CRP level and neutrophil count with disease severity according to mHSS. Patients with HS and increased disease severity exhibited elevated CRP levels and neutrophil counts.…”
Section: Discussionmentioning
confidence: 97%
“…Matusiak et al [31] studied the serum TNF- α levels of 54 patients with HS and observed significantly higher levels in the HS patients compared with the healthy controls. In another study, they also identified the soluble IL-2 receptor as a potential marker of value for determining the severity of HS [32]. These articles initiated the study of serum inflammatory cytokines as biomarkers for HS.…”
Section: Discussionmentioning
confidence: 99%